Effects of shoe type and shoe–pedal interface on the metabolic cost of bicycling. (2nd January 2016) - Straw, Asher H.; Kram, Rodger
Abstract : Cyclists, coaches, and equipment manufacturers claim that cycling-specific shoes coupled with clipless pedals are 'more efficient'. However, scientific evidence supporting or refuting these claims is lacking. We measured the metabolic cost of cycling at sub-maximal power outputs and tested the null hypothesis that there would be no differences between three different shoe-pedal combinations. Eleven healthy subjects participated (six males, four females, age 24.9 ± 6.84 yr, mass 69.98 ± 9.37 kg). We compared: (1) Nike Free 3.0 running shoes with flat rubber pedals, (2) Nike Free 3.0 running shoes with classic aluminium quill pedals, toe clips, and straps, and (3) the cyclists' own rigid-soled, cleated cycling shoes with corresponding clipless pedals. With the three different shoe-pedal conditions in random order, subjects completed three sequential 5-min cycling trials (50, 100, and 150W all at 90RPM) on a custom pan-loaded cycle ergometer equipped with a standard Monark flywheel. Subjects remained seated with both hands placed on the tops of the ergometer's racing-style handlebars. A 5-min rest period separated each of the three sets of trials. We analysed each subject's expired gases and from the rates of oxygen consumption and carbon dioxide production, we calculated metabolic power in watts (W). As hypothesized, there were no significant differences ( p > 0.57) in the metabolic power consumed for pedaling at 50, 100, and 150 W: Nike Free and flat pedals: 445.7, 619.0, and 817.9 W; Nike Free and quill pedals with toe clips: 428.7, 600.7, and 818.0 W and cycling shoes with clipless pedals: 441.6, 612.3, and 806.4 W, respectively. Though cycling shoes may have comfort or safety benefits, they do not enhance efficiency.